Respuesta :

1a.

Answer is 8x² - 2x + 8

  (x² - 4x + 5) + (7x² + 2x + 3)

The parentheses can go away since this is all addition (associative property of addition)

  x² - 4 x + 5 + 7x² + 2x + 3

Combine like terms.

  (x^2 + 7x²) + (-4x + 2x) + (5 + 3)   = 8x² - 2x + 8

======

1b.

Answer is 5x^2 + 7x - 7

  (7x² + 4x - 6) - (2x² - 3x + 1)

Distribute the negative into the right parentheses.

  (7x² + 4x - 6) - (2x² - 3x + 1)

  = 7x² + 4x - 6 - 2x² + 3x - 1

  = (7x² - 2x²) + (4x + 3x) + (-6 - 1)

  =  5x^2 + 7x - 7

ACCESS MORE